Differentiation arrest and stromal cell-independent growth of murine erythroleukemia cells are associated with elevated expression of ets-related genes but not with mutation of p53. - Nibbs, R J (1993)
The ELM erythroleukemia is novel in that long-term survival of leukemic cells in culture (ELM-D cells) is dependent on contact with a bone marrow-derived stromal feeder cell layer. However, a number of stroma-independent (ELM-I) mutants that vary in their ability to differentiate in vitro in response to erythropoietin and interleukin-3 have been derived. We have attempted to define the genetic changes responsible for these different phenotypes. At the p53 locus in the primary leukemic cells, one copy of the gene has been lost whereas the other contains an 18-bp depletion, implicating its mutation as an early step in the development of the leukemia. Changes in ets gene expression have also been found. The Fli-1 gene region is rearranged in the primary tumor because of the insertion of a retrovirus inserted upstream of one Fli-1 allele, but this does not result in Fli-1 gene activation in any of the ELM-D or ELM-I cell lines except one. It seems significant that this line is the only one to have lost the ability to differentiate in response to erythropoietin. In addition, up-regulation of erg is associated with stromal cell-independent growth, since all ELM-I mutants have moderate levels of erg mRNA, whereas only low or undetectable levels are found in primary leukemic cells in vivo or in ELM-D cells in vitro. This up-regulation of erg mRNA seems to be important for stromal cell-independent growth, since ELM-D cells show elevated expression of the erg gene after separation from stromal cells. This seems to be made permanent in ELM-I mutants, since they do not down-regulate erg mRNA when grown in contact with stromal cells. We therefore propose that ets family members regulate both the survival and differentiation of erythroid cells.